Geographical Genetics (MPB-38) - Epperson, Bryan K., 1957- (Book collections on Project MUSE., 2003)
Population genetics has made great strides in applying statistical analysis and mathematical modeling to understand how genes mutate and spread through populations over time. But real populations also live in space. Streams, mountains, and other geographic features often divide populations, limit migration, or otherwise influence gene flow. This book rigorously examines the processes that determine geographic patterns of genetic variation, providing a comprehensive guide to their study and interpretation. Geographical Genetics has a unique focus on the mathematical relationships of spatial stat.